Leica Nova MS50 La prima MultiStation al Mondo - Grimm, David Eugen (GEOmedia, 2013)
In a single unit, with the size and weight of a total station, Leica Nova MS 50 combines the functionali-ty of the total station,  digital imaging, connectivity GNSS and 3D laser scanning. The wellorganized workflow ensures full performance in all phases , from data collection and verification, processing , up to the final results. The new, fast and accurate system to measure the distance reduces the measurement time of up to 50 % and increases the extent of the measure. Thanks to the engine fast, it is possible to obtain a dynamic tracking. The GNSS sensor is fully integrated into the workflow and data structure allowing the direct georeferencing . The setup SmartStation and SmartPole increase the flexibility of application in the field. An advanced  imaging technology, which includes a panoramic camera and a camera coaxial with 30x magnification, allows for accurate image of the relief, the instrument or remotely, and an extensive photographic documentation. 3D laser scanning is fully integrated into the workflow and can be combined with survey data and images. The numerous on-board functionality allow you to get results in the field. Leica Nova MS 50 offers a new dimension in measurement technology which allows the user to make the right decision on the field.